2019
DOI: 10.4317/medoral.23131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of xerostomia on the quality of life of patients submitted to head and neck radiotherapy

Abstract: Background The aim of the present work was to evaluate the impact of xerostomia on the quality of life of patients who underwent radiotherapy in the head and neck region. Material and Methods This was a cross-sectional, quantitative study. The sample comprised 40 patients whose xerostomia was classified through the xerostomia inventory and the quality of life evaluated through the oral health impact profile questionnaire (OHIP). Results The majority of participants were male (75%), mean age 58.7 years. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
2
16
1
2
Order By: Relevance
“…Similar studies have reported that xerostomia significantly reduced OHRQOL. 12 , 29 , 37 Niklander et al. reported a significant difference between OHRQOL and the presence or absence of xerostomia, with a mean S–OHIP score of 20.1 ± 14.32 in the xerostomic group 12 compared to our study, in which comparatively lower median scores were reported on S–OHIP.…”
Section: Discussioncontrasting
confidence: 70%
“…Similar studies have reported that xerostomia significantly reduced OHRQOL. 12 , 29 , 37 Niklander et al. reported a significant difference between OHRQOL and the presence or absence of xerostomia, with a mean S–OHIP score of 20.1 ± 14.32 in the xerostomic group 12 compared to our study, in which comparatively lower median scores were reported on S–OHIP.…”
Section: Discussioncontrasting
confidence: 70%
“…Xerostomia may develop because of salivary gland injury and reduced or absent salivary flow among patients with head and neck cancer (HNC) 1,2 . Xerostomia may lead to oral problems, including pain, dysphagia, speech difficulty, a reduced or altered sense of taste, an increased risk of dental caries, infections, and osteoradionecrosis 3 . Xerostomia has been numbered among the top 5 most severely reported symptoms in patients with long‐term oropharyngeal cancer (OPC) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, 86.8% of people complained of xerostomia more often or always. One study showed that 97.5% of individuals complained of xerostomia at the end of radiotherapy [24]. The xerostomia is one of the most common and unpleasant side effects of radiotherapy of head and neck cancers [25].…”
Section: Discussionmentioning
confidence: 99%